Excitation of Storm Time Pc5 ULF Waves by Ring Current Ions Based on the Drift‐Kinetic Simulation. Issue 4 (18th February 2019) - Yamakawa, T.; Seki, K.; Amano, T.; Takahashi, N.; Miyoshi, Y.
Abstract: Storm time Pc5 waves are considered to be excited through the drift‐bounce resonance by ring current ions associated with the injection from the magnetotail. Using the Geospace Environment Modeling System for Integrated Studies–Ring Current simulation, a drift‐kinetic and self‐consistent model for ring current particles, we investigate the excitation mechanism of these waves in the inner magnetosphere. The power spectra of electromagnetic field fluctuations show the excitation of both poloidal and toroidal mode waves in Pc5 frequency range. It is found that these waves are fundamental mode waves with the azimuthal wave number m − 20 and excited through the drift resonance with the drifting ions with energies of 80–120 keV. The simulation indicates that global distribution of wave power coincides with the positive local growth rate mainly contributed by the positive phase space density gradient in energy. Plain Language Summary: Pc5 ultralow frequency waves are geomagnetic pulsations having frequencies from 1.67 to 6.67 mHz. The excitation mechanism and global distribution of the Pc5 waves is a key to understand dynamic variation of the geospace, since these waves are considered to contribute to the radial transport of radiation belt electrons. These waves can be excited through the wave‐particle interaction with the drifting and bouncing motions of ring current ions (drift‐bounce resonance). Using the Geospace Environment Modeling System for Integrated Studies–Ring Current simulation, a global drift‐kinetic and self‐consistent model for ring current particles, we investigate the excitation mechanism of Pc5 waves in the inner magnetosphere. Pc5 waves are excited through the resonance with the drifting ions with energies of 80–120 keV. Comparison of the wave properties and theory indicates that positive phase space density gradient in energy formed by the drifting injected ions is responsible for the excitation of the Pc5 waves. Key Points: Excitation of storm time Pc5 waves by ion injection is simulated with a global drift‐kinetic simulation of ring current ions (GEMSIS‐RC) Pc5 waves are excited by the drift resonance with ions in the energy of 80–120 keV with peak frequency gradually decreasing from 4 to 2 mHz The wave growth is resultant from the positive PSD gradient in energy considering the injection of protons with the temperature of 16 keV